دراسة مقارنة لخوارزميات الضغط وأثرها على تراسل المعطيات في الشبكات - عجيب دريد (Latakia University Journal -Engineering Sciences Series, 2018)
نظرا للتزايد الكبير لاستخدام تراسل البيانات وخدمات تبادل المعلومات بأنواع مختلفة ضمن بيئات متباينة عتادياً وبرمجياً كان لابد من وجود لغة توصيف مثالية قابلة للتوسع والتطوير تخدم هذه الاحتياجات المتزايدة بأفضل شكل وبأقصر وقت ممكن و كانت اللغة الاكثر انتشاراً والأكثر استخداماً لغة XML. كما أن اعتماد بنية الرسوميات احياناً خلق مشكلة أثرت على أداء شبكات نقل المعلومات نظرا للحجم الكبير للبيانات المتبادلة وكذلك الحاجة لسعة تخزينية كبيرة في طرفي الارسال والاستقبال لذا كان لابد من إيجاد طرق فعالة لإنقاص حجم تلك البيانات التي يتم تبادلها من خلال الشبكة. تم إجراء العديد من الأبحاث العلمية والتجارب العملية حول إيجاد طرق فعالة لإنقاص الحجم الفعلي للبيانات وباعتماد بارامترات مختلفة تؤثر على عملية ضغط الملفات بحيث تحقق نتائج أفضل بالتقليل من حجوم الملفات المتبادلة مع الانتباه الى أزمنة ضغط وفك الضغط للملفات. لذا تم التركيز في هذا البحث على دراسة ومقارنة لبعض خوارزميات الضغط للملفات وبيان أثرها على تراسل البيانات في الشبكات. Due to the large increase in the use of data communication and information exchange services of different types in different environments, the standard and the programming had to be a language of characterization is ideal for scalability and development that serve the growing needs in the best form and in the shortest possible time and was the most widely used language and the most widely used XML language. he adoption of graphics architecture sometimes created a problem affecting the performance of information transmission networks due to the large volume of data exchanged as well as the need for large storage capacity at both ends of the transmission and reception. Effective ways of reducing the amount of data exchanged through the network had to be found. There have been many scientific researches and practical experiments on finding effective ways to reduce the actual size of the data and by adopting different parameters that affect the process of compressing the files so as to achieve better results by reducing the volumes of files exchanged with attention to times of compression and decompression of files. In this research, we focused on the study and comparison of some compression algorithms for files and their effect on data communication in networks.